HYPERTROPHY OF THE HUMAN HEART AT THE LEVEL OF FINE STRUCTURE : An Analysis and Two Postulates - Richter, G. W. (The Rockefeller University Press, 1963)
Muscle cells in the left ventricular walls of four markedly hypertrophied human hearts (above 600 gm) were compared with muscle cells in four non-hypertrophied hearts (up to 310 gm). Blocks of tissue obtained postmortem within 6 hours were processed for light and electron microscopy under conditions suitable for good preservation of myofibrils. A lattice parameter, q(h), was defined as the number of myosin filaments per square micron in either H zones or A bands. By the use of methods of electron microscopy, q(h) was determined for perpendicular cross-sections of A bands in a large number of well preserved myofibrils of muscle cells in both groups of hearts. Statistical evaluation of the distributions of values of q(h) revealed no significant difference between the two groups. Thus, the myofilament lattices in hypertrophied cells were geometrically within normal limits. Planimetric measurements of cross-sectional areas of muscle fibers were made, using photomicrographs obtained from one representative hypertrophied heart and from one control. The size-frequency distribution of the measurements showed a marked difference between the two hearts, and confirmed the presence of hypertrophy of muscle cells. Counts of the number of myofibrils per muscle cell were determined for samples from the same two hearts, evaluated statistically, and found to be significantly higher for the hypertrophied heart. It is proposed (a) that myofibrils in hypertrophied heart muscle cells have filament lattices with geometrical arrangement and macromolecular parameters that are the same as those found in myofibrils of normal heart muscle cells; and (b) that in hypertrophy the number of myofilaments increases through formation of new myofibrils, and possibly also by addition of filaments to preexisting myofibrils.